Perspectivas do setor metal-mecânico na região de Panambi - RS - Guarienti, Adriane (2008)
The survey had as a goal indicate the perspectives of development of the mechanical-metal sector from the region of mechanical Panambi - RS, whose companies develop correlate activities of high and medium technological complexity. The sector, composed by an organizational arrangement, involves several agents who contribute to the empowerment and competitiveness among companies. The identification of agents that configure the arrangement and their inter-relationships permitted to diagnose the problems of the sector. As a method it was used the approach of qualitative research, with collect of data for nonprobabilistic and intentional sample, through unstructured interviews. With the results of the analysis of these data it was possible to present the priorities of development of the sector in the region.